Effects of active vibration control of simply supported plates on sound radiation - Hirschfeldt, Natasha; Furtmüller, Thomas; Adam, Christoph (Frontiers in Built Environment, 2025)
This paper deals with the effects of different active vibration control strategies applied to a vibrating structure on its sound radiation, taking into account the effect of the position of the excitation force. This is done by means of numerical analyses of a simply supported plate, where both the sound pressure field and the radiated sound power are computed for both uncontrolled and controlled systems. Reflections of the sound waves from walls placed around the vibrating plate are considered using the image source method. Although the vibration mitigation of the plate is achieved by active control measures, it does not imply a reduction of the sound propagation. This means that if the vibration of the plate is attenuated, the sound radiated by the plate can be amplified, an effect that is usually undesirable in practice. By simulating different strategies of active control, the study shows that, among the analyzed approaches, direct velocity feedback control provides the best overall reduction in terms of structural vibration and acoustic radiation.